The Plague Files : Crisis Management in Sixteenth-Century Seville - Cook, Alexandra Parma (Book collections on Project MUSE., 2009)
In the first half of the 1580s, Seville, Spain, confronted a series of potentially devastating crises. In three years, the city faced a brush with deadly contagion, including the plague; the billeting of troops in preparation for Philip II's invasion of Portugal; crop failure and famine following drought and locust infestation; an aborted uprising of the Moriscos (Christian converts from Islam); bankruptcy of the municipal government; the threat of pollution and contaminated water; and the disruption of commerce with the Indies. While each of these problems would be formidable on its own, when.